Workshop on Introduction to Bioinformatics in the Fisheries Sector for High School Muhammadiyah Kupang Students - Suleman; Wesly Pasaribu; Welem Turupadang (Jurnal Pengabdian Masyarakat Formosa, 2024)
One field of science that has been developing rapidly in recent decades is the field of bioinformatics. Advances in the rapidly growing field of information technology make it easier for someone to access and analyze information from several database sources that store biological data throughout the world via websites. Apart from that, the distribution of Bioinformatics Application programs via the internet can now help pupils, students, teachers, lecturers and researchers in solving biological problems by using various database sources and software for various needs, including learning needs. Community service activities in the form of training at SMAS Muhammadiyah Kupang were held on Saturday, May 18 2024. The methods used were presentation of material and training related to bioinformatics as well as pre-tests and post-tests to determine students' abilities.